Towards climate-resilient conservation: Integrating genetics and environmental factors in determining adaptive units of a xeric shrub - Yong-Zhi Yang; Pei-Wei Sun; Chong-Yi Ke; Min-Xin Luo; Jui-Tse Chang; Chien-Ti Chao; Run-Hong Gao; Pei-Chun Liao (Global Ecology and Conservation)
Determining management units (MUs) for conservation typically focuses on target organisms' demography dependencies, often neglecting adaptive diversity and evolutionary processes. This study examines the genetic variation of Ammopiptanthus mongolicus, a xeric shrub from eastern Central Asia, to identify genetic traits linked to climate adaptation and delineate seed and breeding zones based on environmental factors. We analyzed RAD-seq data from 217 samples across 19 populations, integrating ecological niche modeling (ENM) and GradientForest (GF) to pinpoint adaptive genetic variations. ENM identified the central-east and west-north regions as optimal habitats, while GF analysis revealed seed and breeding zones based on 1637 climate-adaptive SNPs, indicating significant genetic differentiation linked to temperature and precipitation. Population structure analysis revealed both congruences and discrepancies between genetic and climatic clustering, particularly in peripheral regions, suggesting that adaptive genes may not follow isolation-by-distance rules like neutral genes. Genomic turnover analysis showed significant allelic changes along climatic gradients, highlighting local adaptation to temperature fluctuations. Peripheral populations exhibited higher genetic loads of loss-of-function alleles, indicating rapid adaptation. The study emphasizes the necessity of incorporating adaptive diversity in conservation strategies and recommends establishing MUs that align with adaptive genotypes and climatic conditions. Integrating genomic insights into breeding programs can further enhance the resilience and sustainable management of this vulnerable species.